Examining the relationship between Exposure to Avengers Action Figures and Men’s Body Dissatisfaction and Eating Disorders in Pakistan - Iqbal, Saima; Sultana, Saba; Malik, Amna (Pakistan Journal of Humanities and Social Sciences, 2024)
This study investigates the relationship between social comparison, body dissatisfaction, and eating disorders among males in five major cities of Pakistan. The sample comprised 400 male participants drawn from diverse socioeconomic backgrounds. The Social Comparison Theory serves as the theoretical framework for examining how individuals' perceptions of their bodies are influenced by comparisons with others. Results revealed significant correlations between eating disorder symptoms and body dissatisfaction as well as social comparison tendencies. More specifically, there was a larger tendency toward disordered eating practices and higher degrees of body dissatisfaction among those who participated in upward social comparison. The results emphasis the importance of considering social comparison processes in understanding body image concerns and eating disorders among males in Pakistan. Implications for intervention and prevention efforts aimed at promoting positive body image and healthy eating behaviors are discussed. The implications of these findings extend to intervention and prevention strategies geared towards fostering positive body image and cultivating healthy eating behaviors among this demographic.